ERROR ANALYSIS ON SIMPLE PAST TENSE SENTENCE MADE BY FIRST YEAR STUDENT OF SMPN 2 BANYUDONO BOYOLALI IN 2009/2010 - ANGGRAINI, RIRIN (2011)
This research is aimed of analyzing the kinds of error made by the first year students of SMPN 2 Banyudono Boyolali in learning grammar and structure, describing the most dominant kind of error made by the first year students of SMPN 2 Banyudono Boyolali in learning grammar and structure, and describing the causes of the student's error. This research is a qualitative research. The data are simple past tense sentences consisting errors composed by the students. The subject of the study is first year student of SMPN 2 Banyudono Boyolali and the object of the study is the grammar error especially on simple past tense. The results of study show that there are some error on simple past tense sentences done by the second year student of SMPN 2 Banyudono Boyolali. First, there are three kinds of error made by the student in SMPN 2 Banyudono Boyolali. The kinds of error are: double markings, regularization and simple additions. Second, the most dominant of error made by the First Year Students of SMPN 2 Banyudono Boyolali in learning grammar and structure is double marking. There are 21 students make error on double marking, 3 students on regulation and 1 student on simple addition. The second finding the most dominant of error made by the first year students of SMPN 2 Banyudono Boyolali in learning grammar and structure is in double marking also. There are 22 students make error on double marking, 3 students on regulation and 2 students on simple addition and the last There are some errors caused by the student basically that the students were not really understood about the grammar especially the formulation of simple past tense and the form of Verb1, Verb2, and Verb3. The students also lack in vocabulary, their dictionary incomplete, and how to combine a paragraph word per words.